2006
DOI: 10.1179/joc.2006.18.6.617
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin and Gatifloxacin in an Acid Model of PersistentMycobacterium tuberculosis

Abstract: Studies in the mouse and in humans suggest that use of moxifloxacin and gatifloxacin may shorten the duration of treatment of pulmonary tuberculosis. We describe here the in vitro findings with gatifloxacin and moxifloxacin in regimens similar to those that might be used in the treatment of tuberculosis. The bactericidal activities of moxifloxacin and gatifloxacin were measured alone and in different combinations with isoniazid, rifampicin and pyrazinamide against a 30-day, stationary phase culture, at a pH of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…However, true antagonism between the standard drugs was never observed, and HRZ always showed equivalent or better activity than RZ. Similar to our results, other investigators using models of in vitro (23) and in vivo combination drug efficacy experiments have failed to find antagonism (9). Others have also described better or equivalent activity of HRZ versus RZ (20).…”
Section: Discussionsupporting
confidence: 82%
“…However, true antagonism between the standard drugs was never observed, and HRZ always showed equivalent or better activity than RZ. Similar to our results, other investigators using models of in vitro (23) and in vivo combination drug efficacy experiments have failed to find antagonism (9). Others have also described better or equivalent activity of HRZ versus RZ (20).…”
Section: Discussionsupporting
confidence: 82%
“…In vitro studies and studies in mice showed improved activity of rifampin and isoniazid when gatifloxacin was added and even more when the regimen also included pyrazinamide (26,81,87). Ethambutol interfered with gatifloxacin in vitro as it did with moxifloxacin: it caused a remarkable increase in the MIC 90 of gatifloxacin (87).…”
Section: Ii) Gatifloxacin (A) Mechanism Of Actionmentioning
confidence: 99%
“…The MICs of gatifloxacin against M. tuberculosis range from 0.2 to 0.5 mg/l (Rodriguez et al 2002). In vitro studies and studies in mice showed improved activity of rifampin and isoniazid when gatifloxacin was added, and even more efficacy was noted when the regimen also included pyrazinamide (Kubendiran et al 2006). A multicenter trial is currently enrolling patients at five locations in Africa (Umubyeyi et al 2007).…”
Section: Moxifloxacin and Gatifloxacinmentioning
confidence: 99%